Managing the development of microeconomic systems in the face of global challenges AD ALTA - Галушка, Зоя Іванівна (Чехія / Czech Republic. Web of Science (ESCI), ERIH PLUS, CrossRef, EBSCO, Index Copernicus, 2022)
The study is aimed at improving methodological approaches and methodological tools for studying the functioning and development of microeconomic systems in historical retrospect and in today's post-industrial economy. A system of factors is highlighted, providing conditions are substantiated, and mechanisms for managing microeconomic systems in the face of global changes in the external environment are proposed, based on compliance with paradigm changes, global challenges, global trends in technological development, promising and critical technologies at the national level, priorities and development goals.
Keywords: Actors, Economic system, Microeconomics, Paradigm, Technology.